The Association of Inpatient Occupancy with Hospital‐Acquired Clostridium difficile Infection. Issue 10 (27th June 2018) - Abir, Mahshid; Goldstick, Jason; Malsberger, Rosalie; Setodji, Claude M.; Dev, Sharmistha; Wenger, Neil
Abstract : Few studies have evaluated the relationship between high hospital occupancy and hospital‐acquired complications. We evaluated the association between inpatient occupancy and hospital‐acquired Clostridium difficile infection (CDI) using a novel measure of hospital occupancy. We analyzed administrative data from California hospitals from 2008–2012 for Medicare recipients aged ≥65 years with a discharge diagnosis of acute myocardial infarction, heart failure, or pneumonia. Using daily census data, we constructed patient‐level measures of occupancy on admission day and average occupancy during hospitalization (range: 0‐1), which were split into four groups. We used logistic regression with cluster standard errors to estimate the adjusted and unadjusted relationship of occupancy with hospital‐acquired CDI. Across 327 hospitals, 558, 344 discharges met our inclusion criteria. Higher admission day occupancy was associated with significantly lower adjusted likelihood of CDI. Compared to the 0‐0.25 occupancy group, patients admitted on a day of 0.51‐0.75 occupancy had 0.86 odds of CDI (95% CI 0.75‐0.98). The 0.76‐1.00 admission occupancy group had 0.87 odds of CDI (95% CI 0.75‐1.01). With regard to average occupancy, intermediate levels of occupancy 0.26‐0.50 (odds ratio [OR] = 3.04, 95% CI 2.33‐3.96) and 0.51‐0.75 (OR = 3.28, 95% CI 2.51‐4.28) had over three‐fold increased adjusted odds of CDI relative to the low occupancy group; the high occupancy group did not have significantly different odds of CDI compared to the low occupancy group (OR = 0.96, 95% CI 0.70‐1.31). These findings should prompt exploration of how hospitals react to occupancy changes and how those care processes translate into hospital‐acquired complications in order to inform best practices.